Determination of the Levels of Selected Essential Metals in Sycamore (Ficus sycomorus L) Fruit and Seed Using Flame Atomic Absorption Spectrophotometry - Dessie Ashagrie Tafere; Minbale Admas Teshager (Journal of Chemistry)
Background. Edible wild fruits are nature’s gift to mankind. Considering the growing need to identify alternative bio-nutritional sources, some underutilized species of Ficus sycomorus L. of the family Moraceae were evaluated as wild edible fruits to study its nutritive and mineral composition in order to prioritize its edibility for people. Methods. The concentration of macro (K, Ca, and Mg) and micro essential elements (Fe, Mn, Zn, and Cu) metals in sycamore fruit and seed samples was determined by using a flame atomic absorption spectrophotometer (F AAS). The wet digestion procedure was evaluated using the standard addition (spiking) method, and an acceptable percentage recovery was obtained in the range of 81–119 and 80–118 for the metals in fruit and seed samples, respectively. 0.5 g of oven-dried samples was digested using 10 mL of conc. HNO3 and 5 mL of H2O2 at 110°C for 1 hour. Results. Significant amounts of both the major and trace elements were found in both the fruit and seed samples. The highest levels of macro essential metals, such as Mg (400 ± 10), K (133 ± 3.291), and Ca (33 ± 0.404) all in mg·kg−1, and micro essential elements, such as Fe (5.7 ± 0.5), Zn (2.3 ± 0.55), and Cu (3.6 ± 0.15) all in mg·kg−1, were found in fruit of Ficus sycomorus L., but the concentration of essential metals in seed sample was Mg (333 ± 5.7), K (122 ± 1.6), Ca (31 ± 0.77), Fe (4.19 ± 0.87), Zn (2.06 ± 0.42), and Cu (3.38 ± 0.15) all in mg·kg−1. Mn (3.04 ± 0.16 mg·kg−1) was found in equal amount in both the seed and fruit of F. sycomorus L. Conclusion. In general, the concentration of macro and micro essential metals in F. sycomorus fruits was found; Mg > K > Ca and Fe > Cu > Zn, respectively. Similarly, the concentration of macro and micro essential metals in Ficus sycomorus seeds was found; Mg > K > Ca and Fe > Cu > Zn, respectively. The results were compared with values reported in the literature.